Analisis Dampak Pernikahan Anak Usia Dini Menggunakan Pendekatan Street Level Bureaucracy di Kabupaten Sampang – Madura - Fawaid Fawaid; Dida Rahmadanik; Adi Soesiantoro (Universitas 17 Agustus 1945 Semarang, 2025)
Child marriage remains a serious issue in many regions of Indonesia, including Sampang Regency, Madura. Despite the implementation of laws that set the minimum legal age for marriage, early marriages are still widespread and bring various negative impacts, including educational dropout, reproductive health risks, and socio-economic problems. This study aims to analyze the impact of child marriage using the Street-Level Bureaucracy approach developed by Michael Lipsky (2010). This approach focuses on how front-line policy implementers-such as officials from the Office of Religious Affairs (KUA), Religious Court judges, social service officers, and community leaders-interpret and enforce child marriage prevention policies at the local level. This research employs a qualitative method with data collected through in-depth interviews with policy implementers and affected community members. The findings indicate that policy implementation is heavily influenced by the discretion of street-level bureaucrats and is shaped by local cultural values and social pressures. Variations in how policies are applied lead to inconsistent outcomes in child marriage prevention. The study also highlights that child marriage often results in school dropout, emotional and financial unpreparedness, and reproductive health risks.